The RATF Formula (Kwok's Formula): Exploiting Average Term Frequency in Cross-Language Retrieval - Ari Pirkola; Erkka Leppänen; Kalervo Järvelin (Information Research: An International Electronic Journal)
In an earlier study, we presented a query key goodness scheme, which can be used to separate between good and bad query keys. The scheme is based on the relative average term frequency (RATF) values of query keys. In the present paper, we tested the effectiveness of the scheme in Finnish to English cross-language retrieval in several experiments. Query keys were weighted and queries were reduced based on the RATF values of keys. The tests were carried out in TREC and CLEF document collections using the InQuery retrieval system. The TREC tests indicated that the best RATF-based queries delivered substantial and statistically significant performance improvements, and performed as well as syn-structured queries shown to be effective in many CLIR studies. The CLEF tests indicated the limitations of the use of RATF in CLIR. However, the best RATF-based queries performed better than baseline queries also in the CLEF collection.